Biomechanical Influence of Cartilage Homeostasis in Health and Disease. (15th September 2011) - Bader, D. L.; Salter, D. M.; Chowdhury, T. T.
Abstract : There is an urgent demand for long term solutions to improve osteoarthritis treatments in the ageing population. There are drugs that control the pain but none that stop the progression of the disease in a safe and efficient way. Increased intervention efforts, augmented by early diagnosis and integrated biophysical therapies are therefore needed. Unfortunately, progress has been hampered due to the wide variety of experimental models which examine the effect of mechanical stimuli and inflammatory mediators on signal transduction pathways. Our understanding of the early mechanopathophysiology is poor, particularly the way in which mechanical stimuli influences cell function and regulates matrix synthesis. This makes it difficult to identify reliable targets and design new therapies. In addition, the effect of mechanical loading on matrix turnover is dependent on the nature of the mechanical stimulus. Accumulating evidence suggests that moderate mechanical loading helps to maintain cartilage integrity with a low turnover of matrix constituents. In contrast, nonphysiological mechanical signals are associated with increased cartilage damage and degenerative changes. This review will discuss the pathways regulated by compressive loading regimes and inflammatory signals in animal and in vitro 3D models. Identification of the chondroprotective pathways will reveal novel targets for osteoarthritis treatments.